Markers of Field Cancerization: Proposed Clinical Applications in Prostate Biopsies - Kristina A. Trujillo; Anna C. Jones; Jeffrey K. Griffith; Marco Bisoffi (Prostate Cancer)
Field cancerization denotes the occurrence of genetic, epigenetic, and biochemical aberrations in structurally intact cells in histologically normal tissues adjacent to cancerous lesions. This paper tabulates markers of prostate field cancerization known to date and discusses their potential clinical value in the analysis of prostate biopsies, including diagnosis, monitoring progression during active surveillance, and assessing efficacy of presurgical neoadjuvant and focal therapeutic interventions.